2022
DOI: 10.9778/cmajo.20210131
|View full text |Cite
|
Sign up to set email alerts
|

People who make frequent emergency department visits based on persistence of frequent use in Ontario and Alberta: a retrospective cohort study

Abstract: Background:The factors that underlie persistent frequent visits to the emergency department are poorly understood. This study aimed to characterize people who visit emergency departments frequently in Ontario and Alberta, by number of years of frequent use. Methods:This was a retrospective cohort study aimed at capturing information about patients visiting emergency departments in Ontario and Alberta, Canada, from Apr. 1, 2011, to Mar. 31, 2016. We identified people 18 years or older with frequent emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For instance, interventions like case management have been shown to reduce numbers of ED visits, and may produce overall cost savings [ 48 , 49 ]. Substance and alcohol use presentations are among the factors associated with chronic high ED utilization among people with frequent ED visits, highlighting the clinical importance of the overlap between these two populations [ 50 , 51 ]. Increasing recognition of multiple factors associated with long-term frequent ED utilization (e.g., substance use, homelessness, mental health issues) suggest that screening interventions could enable the early detection of patients at risk and the initiation of preventative interventions that address underlying unmet needs driving high utilization [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, interventions like case management have been shown to reduce numbers of ED visits, and may produce overall cost savings [ 48 , 49 ]. Substance and alcohol use presentations are among the factors associated with chronic high ED utilization among people with frequent ED visits, highlighting the clinical importance of the overlap between these two populations [ 50 , 51 ]. Increasing recognition of multiple factors associated with long-term frequent ED utilization (e.g., substance use, homelessness, mental health issues) suggest that screening interventions could enable the early detection of patients at risk and the initiation of preventative interventions that address underlying unmet needs driving high utilization [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substance and alcohol use presentations are among the factors associated with chronic high ED utilization among people with frequent ED visits, highlighting the clinical importance of the overlap between these two populations [ 50 , 51 ]. Increasing recognition of multiple factors associated with long-term frequent ED utilization (e.g., substance use, homelessness, mental health issues) suggest that screening interventions could enable the early detection of patients at risk and the initiation of preventative interventions that address underlying unmet needs driving high utilization [ 50 , 51 ]. ED visits may be the optimal points of healthcare contact to engage patients with harmful substance use in preventive intervention, and these opportunities are not always recognized [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…High ED users have historically been targeted to reduce ED overcrowding and associated high costs [3]. Patients with psychiatric disorders, including substance-related disorders (SRDs), are among the largest contributors to high ED use [4], which is usually defined as 4+ ED visits/year-a standard benchmark often used, especially in Canadian studies [4,5]. Across Canada, there is a rising trend in both the overall number of ED visits and visits linked to high ED users [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psychiatric disorders, including substance-related disorders (SRDs), are among the largest contributors to high ED use [4], which is usually defined as 4+ ED visits/year-a standard benchmark often used, especially in Canadian studies [4,5]. Across Canada, there is a rising trend in both the overall number of ED visits and visits linked to high ED users [5]. A Quebec study has shown that in 2014-2015, patients with psychiatric disorders used EDs almost twice as often as patients without psychiatric disorders, and 17% of them were high ED users who accounted for close to half of all ED use and hospitalizations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Emergency department (ED) visits have been shown to be a good proxy of health and social services usage [ 23 ]. Canadians, in general, appear to use EDs more frequently than people in other Commonwealth countries [ 24 ] and, in many jurisdictions, the number of emergency department visits attributable to frequent users is increasing [ 25 ]. Patients with complex care needs have particularly high utilization rates of episodic care [ 26 ].…”
Section: Introductionmentioning
confidence: 99%